2019
DOI: 10.15381/rivep.v30i3.16607
|View full text |Cite
|
Sign up to set email alerts
|

Fasciola hepatica y otras parasitosis gastrointestinales en bovinos de doble propósito del municipio Sabana de Torres, Santander, Colombia

Abstract: El propósito de esta investigación fue determinar la prevalencia de Fasciola hepatica y otras parasitosis gastrointestinales en bovinos doble propósito del municipio Sabana de Torres, departamento de Santander, Colombia. Se colectaron 196 muestras fecales y de sangre en 18 fincas de doble propósito. Los animales fueron estratificados en tres grupos etarios: 0-12, 12-24 y >24 meses. Las muestras fecales se procesaron mediante las técnicas coprológicas de McMaster y Dennis, y la presencia de anticuerpos anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
1
4
0
2
Order By: Relevance
“…In Colombia, bovine fascioliasis causes annual losses exceeding US $ 12,483 in the regions of Antioquia, Boyacá, Cundinamarca, Nariño, and Santander [ 20 , 21 , 22 ]. Some studies suggest that Boyacá and Cundinamarca are endemic for this disease because they are places that favor the life cycle of the parasite [ 23 ]. Giraldo-Forero et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Colombia, bovine fascioliasis causes annual losses exceeding US $ 12,483 in the regions of Antioquia, Boyacá, Cundinamarca, Nariño, and Santander [ 20 , 21 , 22 ]. Some studies suggest that Boyacá and Cundinamarca are endemic for this disease because they are places that favor the life cycle of the parasite [ 23 ]. Giraldo-Forero et al .…”
Section: Introductionmentioning
confidence: 99%
“…In Colombia, bovine fascioliasis causes annual losses exceeding US $ 12,483 in the regions of Antioquia, Boyacá, Cundinamarca, Nariño, and Santander [20,21,22]. Some studies suggest that Boyacá and Cundinamarca are endemic for this disease because they are places that favor the life cycle of the parasite [23]. Giraldo-Forero et al (2016) reported a bovine fascioliasis seroprevalence of 39.4% in Cundinamarca, while Pereira et al (2020) pointed to an infection frequency of 23% in the Boyacá region; hence, bovine fascioliasis imposes a high economic burden of veterinary disease on these areas [21,24].…”
Section: Introductionmentioning
confidence: 99%
“…Colombia showed a prevalence of 75.5%, associated with variables such as soil type, feeding system, drinking system, and herd size [28]. Another study conducted in Colombia showed a prevalence of 19.4% [29], confirming that there may be considerable differences in the percentage of infested animals within the same country due to the epidemiological conditions mentioned above. In addition, the risk factors associated with Eimeria spp.…”
Section: Discussionmentioning
confidence: 87%
“…Por lo que, la pérdida económica total en la temporada de estudio fue de USD 16.507.46. (3,4,6,7,8,9,10,11,12,13,14). Del mismo modo, el porcentaje de infección por fascioliasis en ovinos (53.2%) y caprinos (21%) también fue muy alto, superior a lo reportado en otros países (3,4,5), solo inferior a lo hallado en caprinos de Etiopía (6).…”
Section: Rumianteunclassified
“…La fascioliasis es producida por el estado adulto del platelminto trematodo Fasciola hepatica, cuyos hospederos definitivos son los rumiantes; además, del ser humano como hospedero accidental, quienes se infectan por ingerir a la metacercaria (estadio larvario), las cuales se encuentran en el pasto, hierbas o plantas acuáticas que llevan la larva pegada a su extensión (1,2). Al respecto, se ha reportado infección en bovinos, ovinos y caprinos, entre 0.1-38% en Grecia, Irán y Etiopía (3,4,5,6); así como, 0.6-41.5% en países del continente americano (7,8,9,10,11,12,13,14) y 38.2-59.5% en Perú (15,16,17).…”
Section: Introductionunclassified